Collapse : how societies choose to fail or succeed - Diamond, Jared M. (Penguin Books, 2011)
Who Hasn't Gazed upon the abandoned temples of Angkor Wat or the jungle-choked cities of the Maya and wondered, could the same fate happen to us? In this riveting book, Jared Diamond--whose Guns, Germs, and Steel revolutionized our understanding of history--explores how humankind's use and abuse of the environment reveal the truth behind the world's great collapses, from the Anasazi of North America to the Vikings of Greenland to modern Montana. What emerges is a fundamental pattern of environmental catastrophe--one whose warning signs surround us today and that we ignore at our peril. Blending the most recent scientific advances and a vast historical perspective into a narrative that is impossible to put down, Collapse exposes the deepest mysteries of the past even as it offers hope for the future. --